Efek asupan vitamin D terhadap tekanan darah sistolik tikus putih (Rattus norvegicus) - Dessy Hermawan; Sri Kadarsih; Sunarti .; Indwiani Astuti; Zaenal Arifin Nang Agus (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: Hypertension still became potential life threatening disease for human life. The prevalence of hypertension was high and tends to increase. Previous study suggested that there was a linier rise in blood pressure at increasing distances from the equator. More recent study indicated that vitamin D insuffi ciency may be associated with elevated blood pressure.Objective: To investigate the effect of vitamin D intake on blood pressure.Method: This was an experimental study with pre-post test group design. The subjects were 20 male Rattus norvegicus aged 8 weeks. Subjects were divided into 5 groups and each groups received treatment as follow: lived in dark cage and consumed vitamin D free diet for 1 – 13 days, then moved to normal cage (dark-light period) and given vitamin D per-oral of 0.25 μg/kg BW for 1 – 5 days. Data of systolic blood pressure was collected and analyzed with paired t test.Results: The absence of vitamin D in diet caused a signifi cant increase in systolic blood pressure (p=0.01) after 7 days of treatment in dark cage. While oral vitamin D supplementation of 0.25 μg/kg BW caused a signifi cant decline of systolic blood pressure since the fi rst day of vitamin D supplementation and the result appeared stronger after 4 days of treatment (p=0.001).Conclusion: Vitamin D intake had a strong infl uence on systolic blood pressure